Identification of the Insecticidal Effect of Cry Protein on a Variety of Potato Pests - Deshan ZHOU; Doudou YANG; Juan LIU; Weichao LIN; Jie CHENG; Suhua LI (Guangdong nongye kexue)
【Objective】The study was conducted to explore the insecticidal effects of Cry protein on Leptinotarsa decemlineata, Spodoptera frugiperda, and Henosepilachna vigintioctopunctata, aiming to provide a foundation for the development of Cry transgenic potato plants with insect resistance.【Method】'Xisen 6' and 'Favorita 15' potatoes were taken as the test materials and the aforementioned three pest insects as the test subjects. The Cry proteins (Cry1B, Cry1Ac, Cry3A, Cry3B) was applied by using both feed addition and leaf coating methods, and sterile water (CK) and different concentrations of Cry protein treatment groups were set up. The insecticidal effects of the Cry protein on the three insects were identified by comparing the larval mortality rate and biomass among different treatments.【Result】Cry3A protein at concentrations of 10, 20, and 100 μg/g showed significant effects in inhibiting the biomass and increasing the mortality rate of 2nd instar L. decemlineata. In contrast, under the same concentration, there was no significant difference in the biomass of 2nd instar L. decemlineata treated with Cry1B protein compared with the CK, indicating that Cry1B protein had no insecticidal effect on these larvae. Under the treatments with 100 μg/g of Cry1Ac and Cry1B proteins to feed S. frugiperda respectively, the results showed that Cry1Ac protein significantly inhibited the growth of S. frugiperda larvae, while there was no significant difference in larval biomass between the treatments with Cry1B and CK, indicating that Cry1B protein had no insecticidal effect on S. frugiperda. Treatment of 2nd instar H. vigintioctopunctata with 100 μg/g of Cry1B protein exhibited significant effects in inhibiting larval biomass and increasing mortality rate, with the mortality rates on the second day and third day being 50% and 100%, respectively. The results indicated that Cry1B protein had strong insecticidal effect on H. vigintioctopunctata.【Conclusion】Cry1Ac protein has a insecticidal effect on S. frugiperda, Cry3A protein exhibits insecticidal effect on L. decemlineata, and Cry1B protein demonstrates significant insecticidal effect on H. vigintioctopunctata, but it shows no insecticidal effect on L. decemlineata or S. frugiperda.